(untitled) (Research, Society and Development, 2024)
The increasing use of electronic devices, such as smartphones and tablets, has raised concerns about potential impacts on ocular health, especially among children and adolescents. This article offers a critical review of current literature on the effects of prolonged use of these devices on ocular health in this age group. The review covered articles from specialized journals, clinical studies, and systematic reviews from the past 10 years. Findings highlight significant associations between excessive use of digital devices and issues such as eye fatigue, dry eye syndrome, and myopia. Adoption of preventive strategies, such as limiting screen time and promoting outdoor activities, is recommended as measures to mitigate these adverse effects and promote healthy vision among youth. The objective of this study was to investigate the potential adverse effects of prolonged use of electronic devices on the ocular health of children and adolescents through a narrative review of the literature.